(untitled) (Texas Journal of Medical Science, 2022)
Autism Spectrum Disorder is a childhood psychiatric disorder characterized by a variety of cognitive, language and social impairments that can adversely affect the family. ASD are typically characterized by a lack of communication and social skills, accompanied by repetitive patterns of behavior, interest, and activities, and limited communication skills. A new record prevalence rate for autism was released by the National Health Center for Health Statistics. This report said that 1-in-36 children have ASD. Boys’ prevalence is four- to five-fold higher than girls. The exact cause of autism spectrum disorder is yet to be determined. Given the complexity of the disorder and the possibility of varying symptoms and severity, there could be many contributing factors. Genetics and environment may both play a role in the development of ASD. There are a variety of examination tools that pediatricians use in their practices, but the most commonly used one is the Modified Checklist for Autism in Children, Revised with Follow-up (M-CHATR/F). Immunological dysfunction has been linked to ASD in studies on peripheral immune components in people with the disorder. Study objectives were firstly to evaluate the immune system performance in children with ASD, and secondly to determine if some immunological parameters can be used to diagnose ASD. The results showed a significant increase in the level of IL-6 (P <0.001), IL-1β (P><0.01) in ASD children when comparing with the control group. The findings of the current study, suggest the presence of immune dysfunction associated with ASD.>